Biosecurity measures and fear of COVID-19 associated with quality of life at work in healthcare personnel in a hospital - Llerena Torrejón, Antony Alejandro (2022)
Objective: To determine the relationship between biosecurity measures and fear of COVID-19 with quality of life at work in healthcare personnel. Material and methods: Crosssectional analytical study, 245 healthcare workers from the Huaycán Hospital in Lima Peru, who worked during the COVID-19 pandemic, were included. An online survey was applied, during the year 2021, consisting of three questionnaires: biosafety measures, the Fear of COVID-19 Scale to assess fear and another to measure quality of life at work. Chi-square test, Student's t test, Odds Ratio (OR) with 95 % confidence interval (CI) was used, it was considered significant when p < 0.05. Results: The workers had an average age of 38.6 ± 8.5 years, where 68.2 % were women. 61.6 % do comply with biosecurity measures in prevention of COVID-19, 81.6 % have poor quality of life at work, 43.7 % are very afraid of COVID-19 and 48.2 % are afraid of losing their lives due to COVID-19. Staff who were afraid when watching news or stories about COVID-19 were 6 times more at risk for poor quality of life at work (OR: 6.76; 95 % CI: 1.51-30.12), who cannot sleep because they are worried about COVID-19 had 5 times more risk of poor quality of life at work (OR: 5.51; 95 % CI: 1.10- 27.49). Conclusion: Health workers regularly use biosecurity measures, half are afraid of COVID-19; most have poor quality of life, which is associated with fear of seeing news or stories about COVID- 19 and cannot sleep because they are worried about COVID-19.